Gender Gap in Unhealthy Life Expectancy: The Role of Education Among Adults Aged 45+ - Aïda Solé-Auró; Pilar Zueras; Pilar Zueras; Mariona Lozano; Elisenda Rentería (Frontiers Media S.A., 2022)
Objectives: This paper examines the gender gap in unhealthy life expectancy across education levels and age in Spain to understand the extent to which the gender paradox exists over education and across ages.Methods: Death registrations and vital status were taken from the Spanish Statistical Office, while the three health measures (chronic conditions, bad-self rated health and cognitive impairment) from the 2019 European Health Interview Survey. We used Sullivan's method to compute unhealthy life expectancy by education level. We computed the gender and the education ratios of the proportion of unhealthy life years in each health measure by education and age.Results: At almost all ages and all education levels, women significantly lived longer but in poorer health than men. Marked gender differences are seen across most age-groups, particularly among the low educated. We detected greater health inequalities by education level for women (confirming the gender paradox) and a health gradient due to aging and across the health measures charting the disablement process.Conclusion: The new education distribution might improve the unhealthy life expectancy and might reduce the gender gap in the number of years spent in poor health.